2011
DOI: 10.1016/j.cvsm.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Feline Coronavirus in Multicat Environments

Abstract: Feline infectious peritonitis (FIP), a fatal disease in cats worldwide, is caused by FCoV infection, which commonly occurs in multicat environments. The enteric FCoV, referred to as feline enteric virus (FECV), is considered a mostly benign biotype infecting the gut, whereas the FIP virus biotype is considered the highly pathogenic etiologic agent for FIP. Current laboratory tests are unable to distinguish between virus biotypes of FCoV. FECV is highly contagious and easily spreads in multicat environments; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
111
0
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(135 citation statements)
references
References 153 publications
8
111
0
16
Order By: Relevance
“…Several studies have reported that age, breed, sex, and a multi‐cat environment are associated with FCoV infection and development of FIP (Addie et al., ; Bell, Malik, & Norris, ; Sharif et al., ; Worthing et al., ). In the present study, FCoV infection was significantly associated with living environment and age, which is in line with previous studies (Addie et al., ; Drechsler, Alcaraz, Bossong, Collisson, & Diniz, ; Tekelioglu et al., ); the positive rate of FCoV in a multi‐cat environment was higher than that in single cat households. These data suggest that a multi‐cat environment confers a high risk for FCoV infection and development of FIP in China.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have reported that age, breed, sex, and a multi‐cat environment are associated with FCoV infection and development of FIP (Addie et al., ; Bell, Malik, & Norris, ; Sharif et al., ; Worthing et al., ). In the present study, FCoV infection was significantly associated with living environment and age, which is in line with previous studies (Addie et al., ; Drechsler, Alcaraz, Bossong, Collisson, & Diniz, ; Tekelioglu et al., ); the positive rate of FCoV in a multi‐cat environment was higher than that in single cat households. These data suggest that a multi‐cat environment confers a high risk for FCoV infection and development of FIP in China.…”
Section: Discussionsupporting
confidence: 93%
“…Instead, a study in Australia and Malaysia found no association between age and FCoV infection in cats (Bell et al, 2006;Sharif et al, 2009). Household cats living alone had the lowest risk of being FCoV seropositive, as reported in other studies (Addie et al, 2009;Drechsler et al, 2011). In contrast, this study found that household cats that cohabitated with other cats had a high risk of being FCoV seropositive, as has been previously shown (Foley et al, 1997;Herrewegh et al, 1997;Pedersen et al, 2004;Pesteanu-Somogyi et al, 2006;Sharif et al, 2009;Sabshin et al, 2012).…”
Section: Discussionsupporting
confidence: 64%
“…Worldwide the prevalence of FCoV infections may be up to 90% in multi-cat environments and 10-60% in household cats (Herrewegh et al, 1997;Pedersen et al, 2004;Bell et al, 2006;Addie et al, 2009;Sharif et al, 2009;Taharaguchi et al, 2012). Detection of FCoV antibodies in the early stage of infection can be useful to minimize the spread of FCoVs in a breeding cattery, multi-cat household and FCoV-free household (Cave et al, 2004;Dye et al, 2008;Drechsler et al, 2011). Therefore, it is important to monitor cats living in multi-cat environments in order to reduce and control FCoV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the presence or absence of protein-rich effusions in the abdominal and pleural cavities, wet (effusive), dry (noneffusive), and a combination of these two clinical forms (mixed form) of FIP can be distinguished (Drechsler et al, 2011;Hartmann, 2005;Kipar and Meli, 2014;Pedersen, 2009). In natural infections, the wet form seems to be more prevalent than the dry and mixed form, respectively (Pedersen, 2009).…”
Section: Feline Infectious Peritonitis Virusmentioning
confidence: 99%